Identificação da aptidão de áreas à instalação de aterro sanitário no município de Prainha-PA utilizando avaliação multicritério e geotecnologias - NEVES, Shewlyn Jenyele Rodrigues (2022)
In order to contribute to the public administration for the planning and management of municipal solid waste, the present work aims to identify the suitability of areas for the implementation of a sanitary landfill in the municipality of Prainha, located in the Lower Amazon region, in the interior of the state of Pará. For that, this research used the multicriteria analysis based on the Analytical Hierarchical Process (AHP) method through the use of the QGIS software version 3.16.6, an open source Geographic Information System, in which it was geoprocessing of the data relevant to the criteria defined for the evaluation was carried out. Thematic maps were generated that contributed to the elaboration of the final suitability map, in which it was possible to verify the suitability degree of the areas. The final result showed that the areas with the most satisfactory levels of aptitude, those classified as Moderately Good, Good and Great, had a representation of 35.88% of the territory, while 46.40% of the territorial total comprised areas that cannot be under no circumstances for final disposal of solid waste, in accordance with current legislation. It is expected that the results will help guide decision-making, helping to select the most appropriate alternatives from an environmental, operational and socioeconomic point of view. It is worth remembering that the classification regarding the suitability of the areas presented in this work consists of a preliminary evaluation stage, being essential to carry out a subsequent stage of the geoprocessing, carried out in loco, from field work and laboratory tests for the taking of final decision.